Systematic Review of Indonesian Language Learning Management to Improve Academic Writing Skills - Abdul Munir (Pustaka Digital Indonesia, 2025)
Academic writing competence is a fundamental skill in higher education, yet many Indonesian students continue to struggle with producing coherent, well-structured, and properly referenced texts. These challenges underscore the importance of effective learning management in Indonesian language instruction. This study presents a systematic literature review (SLR) of research published between 2019 and 2024 to identify strategies for managing learning processes that enhance academic writing skills. Following the PRISMA 2020 protocol, 32 peer-reviewed articles indexed in Scopus and Web of Science were analyzed. The review reveals four main dimensions of effective learning management: curriculum design, pedagogical strategies, technological integration, and assessment practices. Evidence shows that curricula aligned with academic genres, combined with collaborative and student-centered pedagogies, significantly improve writing outcomes. The integration of digital tools, such as learning management systems and AI-based applications, enhances feedback efficiency, while rubric-based formative assessments ensure transparency and guide student progress. Importantly, the findings emphasize that sustainable improvement in academic writing requires a holistic approach that integrates these dimensions rather than isolated interventions. This study contributes to the discourse on language education management by synthesizing evidence and providing practical recommendations. It suggests embedding academic writing across curricula, strengthening teacher professional development, expanding digital infrastructure, and adopting hybrid feedback systems. Future research should focus on longitudinal, multi-institutional studies and explore the role of emerging technologies in managing writing instruction.